Lifetime drinking history in patients with alcoholic liver disease and patients with alcohol use disorder without liver disease. (3rd July 2017) - Nielsen, Jon Kristinn; Olafsson, Sigurdur; Bergmann, Ottar M.; Runarsdottir, Valgerdur; Hansdottir, Ingunn; Sigurdardottir, Ragna; Björnsson, Einar S.
Abstract: Objective: To determine the differences in lifetime alcohol intake (LAI) and drinking patterns between patients with alcoholic liver disease (ALD) and alcohol use disorder (AUD) without notable liver injury and between males and females with ALD. Methods: Alcohol drinking patterns were assessed using the Lifetime Drinking History (LDH) a validated questionnaire, during an outpatient visit. Patients with AUD, currently in addiction treatment, were matched for gender and age (±5 years) with the ALD group. Results: A total of 39 patients with ALD (26 males and 13 females; median age 58) and equal number of AUD patients were included (median age 56 years). The onset age for alcohol drinking and duration of alcohol consumption was similar in ALD and AUD. The number of drinking days was higher in women with ALD than in women with AUD: 4075 [(3224–6504) versus 2092 (1296–3661), p = .0253]. The LAI and drinks per drinking day (DDD) were not significantly different between patients with ALD and AUD. Females with ALD had lower LAI than males with ALD: 32, 934 (3224–6504) versus 50, 923 (30, 360–82, 195), p = .0385, fewer DDD ( p = .0112), and lower proportion of binge drinking as compared to males with ALD ( p = .0274). Conclusions: The total LAI was similar in patients with ALD and AUD. The number of drinking days over the lifetime was associated with the development of ALD in females. Females with ALD had significantly lower alcohol consumption than men with ALD despite similar duration in years of alcohol intake which supports the concept of female propensity of ALD.